Short Communication: The survival rate and one-year growth of Shorea javanica, Shorea macrobalanos and Hopea mengarawan in coal mined land in Central Bengkulu, Indonesia - WIRYONO WIRYONO; HERY SUHARTOYO; ALI MUNAWAR (Society for Indonesian Biodiversity, 2016)
Wiryono, Suhartoyo H, Munawar A. 2016. Short Communication: The survival rate and one-year growth of Shorea javanica, Shorea macrobalanos and Hopea mengarawan in coal mined land in Central Bengkulu, Indonesia. Biodiversitas 17: 741-745. Dipterocarp trees used to dominate the lowland forest of Sumatra and Kalimantan. Currently, however, dipterocarp trees are rare due to deforestation of natural forest. One major cause of deforestation in Sumatra and Kalimantan is coal mining. Rehabilitation of coal mined soil is usually done using fast-growing alien species. We tried to restore a piece of mined land in Central Bengkulu, using commercially valuable species of Dipterocarpaceae, namely Shorea javanica Koord. & Valet., Shorea macrobalanos Ashton and Hopea mengarawan Miq. In this article, we presented the survival rate and growth of the one year old seedlings of these three species within one year of observation. Of the three species, S. macrobalanos had the highest survival rate (93%), followed by S. javanica (80%) and H. mengarawan (77%). Within a year, the one year old seedlings of S. macrobalanos grew 452% in height, significantly higher than that of S. javanica (221%) and of H. mengarawan (119%). Shorea macrobalanos also had the highest growth in diameter within a year, namely 337%, followed by S. javanica (145%) and H. mengarawan (135%). It can be concluded that within a year of observation, the three species of dipterocarps could grow relatively well in mined land. It is therefore recommended that in the restoration of mined land in Sumatra economically valuable native species of dipterocarps should be used instead of fast-growing alien species.